MAKNA SELIBAT BAKTI MENURUT TEOLOGI TUBUH YOHANES PAULUS II - Gregorius Hertanto Dwi Wibowo; Marianus Ada (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
In light of the rising cases of sexual deviance today, the meaning of consecrated celibacy is frequently questioned and often regarded as contrary to human nature. Furthermore, the declining appreciation for the value of the human body triggers a need for a positive theological foundation for understanding consecrated celibacy. Utilizing a literature study method, the authors intend to examine Pope John Paul II's thoughts on celibacy within his Theology of the Body (TOB). The research results indicate that celibacy is not a rejection of sexuality, but rather a voluntary choice for the sake of the Kingdom of Heaven, rooted in the